ANALISIS MOTIVASI BELAJAR SISWA SMP KELAS VIII MELALUI MEDIA PEMBELAJARAN GEOGEBRA - Hamka Abdul Hakim; Koswara Koswara; Wahyu Setiawan (IKIP Siliwangi, 2019)
This study aims to analyze the learning motivation of class VIII SMP students through Geogebra learning media. The method of this research is quasi research. The research population was 120 class VIII students of SMP Negeri 3 Naringgul. The sample or subject of this study were 28 students. Data collection techniques are non-test or questionnaire. The data collection tool is a questionnaire sheet. The data analysis technique uses descriptive techniques. In general, the results of the research on positive agreement with a high percentage where the Very Agree (SS) response produces an average of 27.2% with the criteria of almost half. Whereas in the Agree (S) and Disagree (TS) responses each with an average of 68.2% with criteria mostly and 6.6% on the criteria for a small part, meaning that it can be concluded that geogebra learning media succeeded in increasing student learning motivation seen from the percentage of Strongly Agree (SS) and Agree (S) responses that are more dominant than the percentage of the Disagree (TS) and Strongly Disagree (STS) responses.